Quality Evaluation of ‘Air-Fried’ and ‘Deep-Fat Fried’ Chicken Ravioli - Tabassum, Aisha; George, R.; Harilal, P.T; Shiby, V. K.; Jayathilakan , K. (Journal of Meat Science, 2019)
The present study aimed to investigate the effect of air frying and deep fat frying on quality attributes of chicken ravioli. Whole wheat flour, ‘’refined wheat flour’’ (maida) and dehydrated chicken powder in the ratio of 40:40:20 was found to be best for the preparation of dough. A ratio of 4:1 was maintained between the dough and stuffing (dehydrated chicken powder) with a dimension of 4×4 cm ensured proper size of the ravioli for effective frying. Weight reduction was observed to be more in air fried sample. The sensory score for air fried sample was 8.07 on 9 point hedonic scale. FFA and TBARS values followed an increasing trend from 0 to 60 days in both samples. The pH of air fried sample decreased from 5.73 to 5.48 in polypropylene (PP) and to 5.51 in laminate of 45 gsm paper / 37.5µ Al foil / 20µ Poly (PFP). In deep fat fried sample it decreased from 5.65 to 5.41 in PP and to 5.42 in PFP. The hardness of air fried chicken ravioli increased during storage from 12N to 26 N and 24N in PP and PFP, respectively. The hardness of deep fat fried chicken ravioli increased from 15N to 26N and 22N in PP and PFP, respectively. The standardized formulation was amenable to both air fried and deep fat fried processes without resulting in any breakage. The physico-chemical changes were less in PFP packed samples than PP packed ones. Both air fried and deep fat fried chicken samples are acceptable up to 60 days at 25±20C. Air fried chicken ravioli can be considered as a healthy alternative to deep fat fried chicken ravioli.